YOUTH MOVEMENT AND ISLAMIC LIBERALISM IN INDONESIA - Herdi Sahrasad (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2020)
This article examines dynamics of Islamic discourses in Post-New Order Indonesia, focusing on the birth of Jaringan Islam Liberal/JIL (Islamic Liberalism Network). The network which emerged in 2001 was a result of informal meeting and group discussions of young intellectuals at Jl. Utan Kayu 68 H, East Jakarta who later agreed to establish the JIL. Since its earliest foundation, the networks has been at the forefront to attack Islamic extremist and fundamentalist groups while calling for Islamic liberalism. This article tries to portray the emergence of the JIL and its liberalism agenda and offers the contestation on Islamic liberalism in Indonesia. As for the latter, it not only encapsulates responses of fundamentalist groups, but also important Muslim organisation, like the traditionalist Nahdlatul Ulama/NU and the Modernist Muhammadiyah, and important Indonesian Muslim thinkers. This article further argues that Islamic liberalism that takes its root to Muslim activism during the New Order Indonesia has shaken the basic foundation of religion as introducing liberalism in Islamic discourses. It has invited contestation and responses for a significant Muslim group, including the two-most important Indonesian Muslim organisations, the NU and the Muhammadiyah. As this article further demonstrates, the contestation is mainly because of different opinions among Muslims on the limit of reason to understand religion.